Islamic Religious Education Teachers' Strategies in Implementing a Multiple Intelligence-Based Kinesthetic Approach at State Senior High School 2 Palembang - Fitriyanti Fitriyanti; Meli Puspita; Yelna Septiana; Zuhdiyah Zuhdiyah; Asri Karolina (Journal of Educational Sciences, 2026)
Islamic Religious Education (PAI) learning at the senior high school level requires active and inclusive approaches to accommodate students’ diverse intelligence profiles and to promote comprehensive internalization of Islamic values. One relevant approach is kinesthetic learning based on multiple intelligences. This study aims to analyze the strategies employed by PAI teachers in designing, implementing, and evaluating kinesthetic learning based on multiple intelligences at SMA Negeri 2 Palembang, as well as to identify its impact on students’ engagement and understanding. This research adopts a qualitative method with a case study approach. The findings indicate that PAI teachers integrate kinesthetic approaches with bodily-kinesthetic, interpersonal, and intrapersonal intelligences through activities such as Islamic history role-playing, Qur’anic memorization through movement, and collaborative group work. Despite challenges related to classroom management and limited facilities, these strategies effectively enhance students’ participation and internalization of religious values. The study concludes that the effectiveness of kinesthetic learning in Islamic education largely depends on teachers’ creativity, the alignment of instructional models with students’ intelligence profiles, and sustained institutional support and pedagogical training.